Root Cause Detection for Excess Control Rod Vibration in Fuel Injection Pump Using Shainin Methodology - Sherugar, Shivdarshan; Jaychandran, K (International Journal of Engineering and Technology, 2018)
Fuel Injection Pump (FIP) is one of the important component of any engine and any issue related to FIP will directly affect the engine. One such issue is excess vibration at full load in multi-cylinder fuel injection pump. Many problem-solving techniques are used in manufacturing industries to reduce rejection rate caused in production line and to improve quality of a product. This study mainly focuses on shainin methodology integrated with six sigma DMAIC, in which various steps were followed to detect and validate the root cause for causing excess vibration of control rod in A-type fuel injection pump.